Bone Marrow Stem Cell Treatment for Ischemic Heart Disease in Patients with No Option of Revascularization: A Systematic Review and Meta-Analysis. - Sheila A Fisher; Carolyn Dorée; Susan J Brunskill; Anthony Mathur; Enca Martin-Rendon (PLoS ONE)
Objective To evaluate bone marrow stem cell treatment (BMSC) in patients with ischemic heart disease (IHD) and no option of revascularization. Background Autologous BMSC therapy has emerged as a novel approach to treat patients with acute myocardial infarction or chronic ischemia and heart failure following percutaneous or surgical revascularization, respectively. However, the effect of the treatment has not been systematic evaluated in patients who are not eligible for revascularization. Methods MEDLINE (1950-2012), EMBASE (1980-2012), CENTRAL (The Cochrane Library 2012, Issue 8) and ongoing trial databases were searched for relevant randomized controlled trials. Trials where participants were diagnosed with IHD, with no option for revascularization and who received any dose of stem cells by any delivery route were selected for inclusion. Study and participant characteristics, details of the intervention and comparator, and outcomes measured were recorded by two reviewers independently. Primary outcome measures were defined as mortality and measures of angina; secondary outcomes were heart failure, quality of life measures, exercise/performance and left ventricular ejection fraction (LVEF). Results Nine trials were eligible for inclusion. BMSC treatment significantly reduced the risk of mortality (Relative Risk 0.33; 95% Confidence Interval 0.17 to 0.65; P = 0.001). Patients who received BMSC showed a significantly greater improvement in CCS angina class (Mean Difference -0.55; 95% Confidence Interval -1.00 to -0.10; P = 0.02) and significantly fewer angina episodes per week at the end of the trial (Mean Difference -5.21; 95% Confidence Interval -7.35 to -3.07; P<0.00001) than those who received no BMSC. In addition, the treatment significantly improved quality of life, exercise/performance and LVEF in these patients. Conclusions BMSC treatment has significant clinical benefit as stand-alone treatment in patients with IHD and no other treatment option. These results require confirmation in large well-powered trials with long-term follow-up to fully evaluate the clinical efficacy of this treatment.